Bangladesh : whose ideas, whose interests? - Wood, Geoffrey D. (Dhaka, 1994)
Bangladesh: Whose Ideas, Whose Interests? is a gathering together of various writings since 1974 by Geoffrey D. Wood on rural development issues in Bangladesh. Several of the chapters have been written specifically for this volume while others have been appropriately edited. A third of it has been written since 1992. The chapters derive from a combination of primary academic research, action-research, programme specific studies, consultancy reports and more reflective policy discussions that have been carried out in conjunction with academic institutions in Bangladesh, with local NGOs and with donor agencies. They address fundamental processes of agrarian structural change and their gender implications; opportunities for wider participation by landless men and women in agricultural growth; the social implications of rural works and fish culture programmes; rural institutions and poverty alleviation; and broader institutional questions arising from the interaction between state, market and community (including NGOs) concerning corruption, good governance and the franchise state. The 22 chapters are organised into 6 parts to reflect these themes. Throughout the volume there is long range, but grounded speculation which connect processes of 'rurbanisation' to patterns of land use and shifting sets of opportunities for poor economic actors. The volume opens with an introduction which explores the relationship between applied social science and the policy process with various illustrations taken from the material in the book. It concludes in an almost confessional way by offering eleven working principles as a guide through the development maze of poverty alleviation in Bangladesh. The principles focus upon the agenda of rights, governance, democracy, organisational culture, realistic expectations about NGO performance, and portfolio character of people's lives.
Keywords: Rural development